Regulator of G-protein signaling 1 critically supports CD8+ TRM cell-mediated intestinal immunity - von Werdt, Diego; Gungor, Bilgi; Barreto de Albuquerque, Juliana; Gruber, Thomas; Zysset, Daniel; Kwong Chung, Cheong K. C.; Corrêa-Ferreira, Antonia; Berchtold, Regina; Page, Nicolas; Schenk, Mirjam; Kehrl, John H.; Merkler, Doron; et al. (Frontiers in Immunology, 2023)
Members of the Regulator of G-protein signaling (Rgs) family regulate the extent and timing of G protein signaling by increasing the GTPase activity of G protein subunits. The Rgs family member Rgs1 is one of the most up-regulated genes in tissue-resident memory (TRM) T cells when compared to their circulating T cell counterparts. Functionally, Rgs1 preferentially deactivates Gq, and Gi protein subunits and can therefore also attenuate chemokine receptor-mediated immune cell trafficking. The impact of Rgs1 expression on tissue-resident T cell generation, their maintenance, and the immunosurveillance of barrier tissues, however, is only incompletely understood. Here we report that Rgs1 expression is readily induced in naïve OT-I T cells in vivo following intestinal infection with Listeria monocytogenes-OVA. In bone marrow chimeras, Rgs1-/- and Rgs1+/+ T cells were generally present in comparable frequencies in distinct T cell subsets of the intestinal mucosa, mesenteric lymph nodes, and spleen. After intestinal infection with Listeria monocytogenes-OVA, however, OT-I Rgs1+/+ T cells outnumbered the co-transferred OT-I Rgs1-/- T cells in the small intestinal mucosa already early after infection. The underrepresentation of the OT-I Rgs1-/- T cells persisted to become even more pronounced during the memory phase (d30 post-infection). Remarkably, upon intestinal reinfection, mice with intestinal OT-I Rgs1+/+ TRM cells were able to prevent the systemic dissemination of the pathogen more efficiently than those with OT-I Rgs1-/- TRM cells. While the underlying mechanisms are not fully elucidated yet, these data thus identify Rgs1 as a critical regulator for the generation and maintenance of tissue-resident CD8+ T cells as a prerequisite for efficient local immunosurveillance in barrier tissues in case of reinfections with potential pathogens.